2002
DOI: 10.1185/030079902125000822
|View full text |Cite
|
Sign up to set email alerts
|

The Diabcare-Asia 1998 Study -Outcomes on Control and Complications in Type 1 and Type 2 Diabetic Patients

Abstract: The Inadequate metabolic and hypertension control, especially in type 2 patients, needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
2
17
3
Order By: Relevance
“…For example, the mean age at onset was 13.6 years among 49 027 T1D patients followed by the German Diabetes Documentation System, whereas the T1D Exchange study, which has followed thousands of patients in the US, reported a median age at diagnosis of 9.0 years . Nonetheless, comparing the characteristics of patients with T1D in the present study with those in the Diab‐care Asia study, an observational study performed in 230 diabetic centers in 12 Asian regions, shows similarities in the age at onset (27.5 vs 29.2, respectively) and in the peak onset age groups (between 20–29 years in both studies). In the present study, disease onset was after 20 years of age in 69.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mean age at onset was 13.6 years among 49 027 T1D patients followed by the German Diabetes Documentation System, whereas the T1D Exchange study, which has followed thousands of patients in the US, reported a median age at diagnosis of 9.0 years . Nonetheless, comparing the characteristics of patients with T1D in the present study with those in the Diab‐care Asia study, an observational study performed in 230 diabetic centers in 12 Asian regions, shows similarities in the age at onset (27.5 vs 29.2, respectively) and in the peak onset age groups (between 20–29 years in both studies). In the present study, disease onset was after 20 years of age in 69.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The average HbA1c levels in other countries have been reported to range from 7.5% to 8.6% (17)(18)(19)(20)(21)(22)(23)(24)(25). However, glycemic control in Asian patients with DM is generally poor (23)(24)(25), whereas the average level of glycemic control in Japan is fair (2,3). One study (2) reported that the mean HbA1c level in 16,934 Japanese patients with DM in 2002 was 7.5%, while another study (3) showed that the mean HbA1c level in 15,652 Japanese DM patients in 2006 was 7.2%.…”
Section: Discussionmentioning
confidence: 99%
“…This project was initiated in 1997 in 6 countries and subsequently extended to 11 countries in 1998. [7] In 2001, DiabCare India was first published which involved patients from primary health care sectors,[8] and in 2003, DiabCare Asia collected information of patients managed by specialist's care. [9] DiabCare India 2011 was initiated with the aim to evaluate the current Status of diabetes management, its control and complication ten years after the completion of the last DiabCare study in India.…”
Section: Introductionmentioning
confidence: 99%